Virtual teaching assistant for undergraduate students using natural language processing & deep learning - Sakib, Sadman Jashim; Joy, Baktiar Kabir; Rydha, Zahin; Nuruzzaman, Md.; Anik, Khaled Ahmmed (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.